2006
DOI: 10.1002/adma.200502099
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Emission Control in Micropillar Cavities Containing a Fluorescent Molecular Dye

Abstract: Microcavity micropillars are structures composed of two high-reflectivity distributed Bragg reflectors (DBRs) placed either side of an active dipole emitter. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This structure is then vertically etched to form a pillar. The three-dimensional confinement of the optical field within a micropillar has profound effects on fundamental light-emission processes. The most important of these results from reduced-mode volume (termed the Purcell Effect [17] ), which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
1
31
2
Order By: Relevance
“…Such increases in cavity Q factor can be readily achieved by creating structures based on two distributed Bragg reflectors, 32 or by creating microcavities based on a micropillar-type geometry. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Such increases in cavity Q factor can be readily achieved by creating structures based on two distributed Bragg reflectors, 32 or by creating microcavities based on a micropillar-type geometry. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Here, Adawi et al. first reported the fabrication of a micropillar microcavity containing a fluorescent molecular dye using an ion‐beam etching technique . Using near‐field optical imaging techniques, it was shown that such structures were able to modify spontaneous emission rates.…”
Section: Introductionmentioning
confidence: 99%
“…Schwab [115] presented that the altered SE depends on excitation intensity. Adawi [116] and Bennett [117] also found Purcell effect in pillar microcavity. Recently, using a QD weakly coupled to a micropillar cavity, a single photon sources with an indistinguishability of 90% was reported by Ates [118].…”
Section: Se Control In Microcavities and Metallic Nanostructuresmentioning
confidence: 91%